Association between Air Pollution and Risk of Hospital Admission for Pediatric Pneumonia in a Tropical City, Kaohsiung, Taiwan - Peng-Huei Liu; Kuo-Chen Huang; Yu-Lun Tseng; I-Min Chiu; Hsiu-Yung Pan; Fu-Jen Cheng (Aerosol and Air Quality Research)
Abstract Recent evidences have shown that particulate matter (PM) and other air pollutants are associated with pulmonary and systemic inflammation; however, the relationship between air pollutants and the risk of admission for pediatric pneumonia has not been well surveyed. This study aimed to estimate the hazards of air pollutants on the risk of pediatric pneumonia emergency department (ED) visits and hospitalization. Data on PM2.5 (PM with an aerodynamic diameter smaller than 2.5 µm), PM10 (PM with an aerodynamic diameter smaller than 10 µm), sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3) in each of the 11 air monitoring stations in Kaohsiung city were collected. The medical records of non-traumatic patients under 17 years of age who had visited the ED between 2008 to 2013, with a principal diagnosis of pneumonia were extracted. We evaluated the relationship between air pollutant exposure and the risk of admission and length of hospital stay (LOS). An interquartile range increments of PM2.5 (odds ratio [OR]: 1.677, 95% confidence interval [CI]: 1.381–2.041), PM10 (OR: 1.568, 95% CI: 1.312–1.880), NO2 (OR: 1.383, 95% CI: 1.179–1.625), SO2 (OR: 1.261, 95% CI: 1.170–1.361), and O3 (OR: 1.182, 95% CI: 1.024–1.366) were statistically significantly associated with the risk of pediatric pneumonia hospitalization on lag 0–3. In the two-pollutant model, after adjusting for NO2 (OR: 1.534, 95% CI: 1.206–1.958), SO2 (OR: 1.534, 95% CI: 1.206–1.958), or O3 (OR: 1.741, 95% CI: 1.385–2.196), PM2.5 was still statistically significantly associated with pediatric pneumonia hospitalization. Furthermore, higher PM2.5 concentration (> 45 µg m–3) was associated with prolonged hospital LOS (OR: 0.217, 95% CI: 0.03–0.404, P = 0.023), especially for younger children (≤ 5 years). In conclusion, we found that PM2.5, PM10, and SO2 exposure were risk factors for hospitalization due to pediatric pneumonia.